2023
DOI: 10.1021/acs.inorgchem.3c00004
|View full text |Cite
|
Sign up to set email alerts
|

Syndiospecific Copolymerization of Styrene with para-Methoxystyrene Catalyzed by Functionalized Fluorenyl-Ligated Rare-Earth Metal Complexes

Abstract: The development of efficient catalysts for the copolymerization of nonpolar monomers with polar monomers remains a great challenging task in polymer synthesis. A one-pot reaction of anhydrous LnCl 3 with pyridyl-methylene-functionalized octamethylfluorenyl lithium OctFlu-CH 2 PyLi in a 1:1 molar ratio, followed by alkylation with 2 equiv of LiCH 2 SiMe 3 in THF afforded the fluorenyl-ligated rare-earth metal bis(alkyl) complexes (OctFlu-CH 2 Py)Ln(CH 2 SiMe 3 ) 2 (THF) [Ln = Sc (1), Y (2)]. Both complexes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Notably, among various approaches, the coordination copolymerization of polar and nonpolar olefins has been extensively investigated by using various transition metal catalysts since it is a straightforward and atom-efficient strategy for synthesis of functional polyolefin materials . In this content, it is noteworthy that rare-earth alkyl catalysts have emerged as a new class of highly efficient catalysts for the copolymerization of a wide range of polar and nonpolar olefins in the past decade. As we know, precise control of monomer sequence in the primary structure of functional polyolefins is crucial, as it will dictate subsequent secondary and tertiary structures, as well as final properties . Despite considerable efforts, most reported rare-earth-catalyzed coordination copolymerizations of polar and nonpolar olefins have resulted in block or random copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, among various approaches, the coordination copolymerization of polar and nonpolar olefins has been extensively investigated by using various transition metal catalysts since it is a straightforward and atom-efficient strategy for synthesis of functional polyolefin materials . In this content, it is noteworthy that rare-earth alkyl catalysts have emerged as a new class of highly efficient catalysts for the copolymerization of a wide range of polar and nonpolar olefins in the past decade. As we know, precise control of monomer sequence in the primary structure of functional polyolefins is crucial, as it will dictate subsequent secondary and tertiary structures, as well as final properties . Despite considerable efforts, most reported rare-earth-catalyzed coordination copolymerizations of polar and nonpolar olefins have resulted in block or random copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…3,20 Recently, high oxyphilic rare-earth catalysts having a high coordination number exhibit both high activities and high regio-/stereo-selectivities in the polymerization of POs such as polar styrenes, polar α-olefins, or polar dienes and copolymerization with non-polar olefins, affording regio-/ stereo-regular poly(PO)s with the adjustable content of POs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The mechanism of heteroatom-assisted synergistic coordination mode or heteroatom dynamic reversion coordination mode explains that instead of occupying all the empty coordination sites to cause deactivation, the preferential coordination of heteroatoms toward the metal center reduces the oxophilicity of the metal center and facilitates the coordination and insertion of CvC bonds to finally afford poly(PO)s (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, precisely controlled polymerization of styrene and its derivatives had made significant progress by using rare-earth metal catalysts. A variety of well-defined rare-earth metal catalysts sprung up, which showed high activity and perfect regioselectivity in both the homo- and copolymerization of styrene monomers. The first examples of highly syndiospecific styrene polymerization mediated by rare-earth metal was reported almost simultaneously by the groups of Hou and Carpentier. , Cui’s group designed a series of constrained-geometry-configuration (CGC) type rare-earth metal complexes, which behaved well in styrene polymerization. , More interestingly, these complexes exhibited excellent performances in the polymerization of polar styrene monomers. , Isotactic polymerization of styrene monomers can be achieved by rare-earth metal catalysts as well. Carpentier et al first reported the highly isotactic polymerization of styrene initiated by rare-earth metal complexes in 2007 .…”
Section: Introductionmentioning
confidence: 99%